PENERAPAN PASAL 4 UNDANG-UNDANG NO.8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN PADA JASA PENGIRIMAN DOKUMEN DI PT. KERTA GAYA PUSAKA PERWAKILAN PURWOKERTO - Salami, Rochani Urip; Nurjaya, I Ketut Karmi; Kartika, Krisnhoe (Faculty of Law, Universitas Jenderal Soedirman, 2008)
Nowadays, the issue of consumer protection in Indonesia has encompassed various fields of social life, nd without any exemption, the isuue of transportation is include thereof. Transportation is one of the factor that able to determine the succes of state’s economic. Transportation is executable through land, air and water. One of the forms of services in land transportation is the transport of package in Purwokerto that run the area of document. This research usesd the method of normative approach, eith the intention to conclude the legal protection toward the consumer of PT Kerta Gaya Pustaka package transport service branch in Purwokerto, considering that PT Kerta Gaya Pustaka is one of the parties in the world of bussiness that has obligations to perform its bussiness in conformity with the principles and provisions in the consumer protection act (UUPK) as well as possible and with liabilities. Kata Kunci : Perlindungan Konsumen, jasa Pengiriman dokumen